Classroom Discourse Structures: A Comparative Study of Formal and Non-Formal Education at Different Student Levels - Laelatul Abidah; Hamzah Hamzah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Classroom discourse varies based on the interactions between teachers and students, influencing the structure and effectiveness of teaching and learning. A well-structured classroom discourse fosters an organized teaching pattern and facilitates learning. This study analyzed the structure of classroom discourse in English classes across formal (Junior and Senior High Schools) and non-formal (English courses) education settings. A qualitative research design was employed, involving participants from second-grade classes in Junior and Senior High Schools and basic and advanced levels in English courses. Data were collected from transcripts of 20 lessons, covering interactions from opening to closing, and analyzed using the Sinclair and Coulthard model, which organizes discourse hierarchically into ranks: lesson, transaction, exchange, move, and act. The findings showed that non-formal education (basic and advanced English courses) exhibited a higher frequency of all five discourse ranks compared to formal education settings (Junior and Senior High Schools). Non-formal settings also demonstrated more complete discourse stages—opening, body, and closing—indicating a more structured interaction pattern. These results suggest that non-formal education may provide a more conducive environment for student participation and interaction, potentially benefiting language acquisition. The study underscores the effectiveness of non-formal education settings in fostering structured classroom discourse. Further research should explore specific teaching strategies in non-formal settings to enhance interaction and learning outcomes in formal education contexts.